Integration of environmental performance in a virtual reality framework: case study of Putrajaya - Jahn Kassim, Puteri Shireen; Ali, Maisarah; Abdul Majid, Noor Hanita; Ibrahim, Md. Najib (2008)
Microclimate studies are commonly required for new projects especially urban masterplanning that involves the development of a sizeable area within a city. Basically data from microclimate studies gathered from semioutdoor spaces i.e. on airflow, sunlight, lighting and irradiation are typically gathered through field measurements and environment simulation tools are used to enhance the understanding of comfort issues in urban environments in order to assist in design decision making. Simulation and field studies generally generate large amounts of data i.e. numerical and graphical. The aim is towards organising such data such that impact on users as they move through space is presented the sequence in order to increase understanding of comfort and perception from a pedestrian viewpoint. In this paper, virtual reality (VR) used to integrate environmental data gathered from an environmental study of selected areas in the Putrajaya central boulevard to be presented in sequence and link to sensations arising from the variations in the external environment. The focus is on urban design issues related to human comfort and experience of urban spaces, particularly in the context of hot, humid climates. In this climate, the shading issues, heat gain and radiation are a critical issue that has to be assessed through simulation and field work. However V. R can be useful to analyse such open areas or areas between buildings whose microclimate are considerably affected by the insertion of the building mass in the urban fabric. The synchronized-data can be displayed as "gauges" in animated sequence or real time. As the 'user' walks through the spaces in the VR, the line graphs on the gauges will change to indicate the variations in the environmental parameters such as light, air speed and temperature experienced in urban microclimates.